Safety and effectiveness of lumacaftor-ivacaftor in adults with cystic fibrosis: A single-center Canadian experience. Issue 3 (2nd July 2020) - Sergeev, Valentine; Desai, Sameer; Flores, Eri; Kerr, Jane; Su, Victoria; Wilcox, Pearce; Quon, Bradley S.
Abstract: RATIONALE: Lumacaftor-ivacaftor (LUM-IVA) was approved for use in Canada in January 2016. Observational studies have reported a higher incidence of treatment-emergent adverse events (AEs) leading to treatment discontinuation compared to clinical trials. There is still limited data about long-term tolerability and rates of discontinuation in patients who would not have met clinical trial eligibility criteria. OBJECTIVE: To assess the long-term safety and effectiveness of LUM-IVA in a real-world setting. METHODS: We conducted a single-center retrospective cohort study at St. Paul's Hospital (Vancouver, Canada). We tracked changes in percent-predicted FEV1 (ppFEV1), body mass index (BMI), sweat chloride concentration, blood pressure (BP) and pulmonary exacerbations pre- and post-initiation of LUM-IVA. We noted AEs and treatment discontinuations. RESULTS: Of 22 patients who started on LUM-IVA as part of routine clinical care, 10 (45%) discontinued therapy after a median of 3.3 months. At initiation, median (IQR) ppFEV1 was 40.1% (32.7%, 55.9%). Respiratory-related symptoms were the most common AEs (59%). We observed a statistically significant increase in BP ( p  = 0.004). Respiratory-related symptoms and increased BP were the most common reasons for treatment discontinuation, including one instance of hypertensive emergency. There was no change in the median rate of ppFEV1 decline or BMI change despite a statistically significant decrease in sweat chloride concentration 3 months' post-initiation ( p  < 0.001). CONCLUSION: The rate of LUM-IVA discontinuation in this adult cystic fibrosis (CF) cohort was high and similar to other observational studies, but we also report cases of increased BP leading to treatment discontinuation. We recommend long-term monitoring of blood pressure for patients on LUM-IVA.